Implementasi Algoritma A-Star dalam Menentukan Rute Terpendek Destinasi Wisata Kota Malang - Riyan Fahmi Syihabuddin; Mohammad Nafie Jauhari; Muhammad Khudzaifah; Hisyam Fahmi (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Traveling is one of the needs of everyone to relax the mind from the busyness that is lived every day. One of the cities in East Java which is a prima donna for traveling is Malang. The city has approximately 43 tourist destinations. Usually, tourists who want to visit not only one place, but several places. generate assistance in deciding which destinations to visit first in order for their trip to be effective. The shortest search process in this study uses the A-Star Algorithm, one of the BFS algorithms which in the process really considers the heuristic value. The process of testing the shortest route is done by selecting a starting point, then selecting several tourist locations. Next, the shortest route will be searched using the A-star algorithm at each destination, then which destination will be visited first. And so on until the final destination. The effectiveness of the route which involves comparison with the route presented by google maps. Based on the results of 30 experiments on several comprehensive destinations, it was found that the average route search using the A-Star algorithm was 44.17% shorter than that presented on google maps. This is due to the uniqueness of the algorithm in which there is a heuristic value and selection for each destination so as to make the route more effective.